"Is rugby bad for your intellect": the effect of repetitive mild head injuries on the cognitive functioning of university level rugby players - Smith, Ian Patrick (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
The study sought to determine whether there is evidence for the presence of residual (chronic) deleterious effects on cognition due to repetitive mild traumatic brain injury in top team university level rugby players, using ImPACT 3.0, Trail Making Test (TMT) and Digit Span. The initial sample of 48 participants was divided into groups; Rugby (n = 30) and Controls (n = 18), Rugby Forwards (n = 14) and Rugby Backs (n = 16). A reduced sample (N = 31) comprised of Rugby (n = 20) and Controls (n = 11), Rugby Forwards (n = 9) and Rugby Backs (n = 11). Comparative subgroups were equivalent for estimated IQ but not for age and educational level in the full sample; in the reduced sample there was equivalence for all three variables of age, education and estimated IQ. All cognitive test measures were subjected to independent t-test analyses between groups at the pre- and post-season, and dependent t-test analyses for Rugby and Controls at pre- versus post-season. Overall, the results implicated the presence of deleterious effects of concussive events on Rugby players in the areas of speed of information processing, working memory and impulse control. Significant practice effects were found on the TMT and Digit Span for controls, but not on ImPACT 3.0, supporting the use of this computer-based programme in the sports management context.
Keywords: Rugby football injuries; Brain damage; Neuropsychological tests Head -- Wounds and injuries -- Complications; Sports injuries -- Psychological aspects